Introducing a Guide in Physical Therapy Addressing Sexual Function in Adults with Neuromuscular Disorders. (1st August 2022) - Fisette-Paulhus, I; Morin, M; Fortin, J; Girard-Côté, L; Gagnon, C
ABSTRACT: Introduction: Physical therapists are part of the rehabilitation team following individuals with neuromuscular disorders (NMD). Due to their impairments, people with NMD can have difficulties engaging in sexual activities. One study reported that 70% of people living with chronic disorders present difficulties related to sexuality and only 18% can overcome them by themselves [1]. Objective: The guide has 3 main objectives: 1) To document interventions regarding sexual impairments in people with NMD that can be applied by physical therapists in clinical practice; 2) To propose approaches for addressing sexuality with their clients; 3) To highlight issues that require advanced physical therapy expertise in pelvic floor rehabilitation. Methods: The guide is based on a review of the literature and the clinical experience of physical therapists with expertise in NMD or sexuality in Canada. It was developed using the "Rare knowledge mining methodological framework" [2]. Two frameworks were also followed: "Essential Competency Profile for Physiotherapists in Canada (2017)" [3] and the "EX-PLISSIT model" [4, 5]. Results: A total of 75 articles retrieved were considered in our review. Twelve physical therapists and four other health professionals were consulted for this guide. It is recommended to introduce the topic of sexuality early in therapy and follow the steps of the EX-PLISSIT model [4, 5] before offering specific suggestions. Physical therapists should address different aspects in their assessment: interpersonal relationships, assistance required or not during sexual activities, urinary, vaginal or anorectal symptoms, erectile dysfunction, pain, fatigue and impact of the disease on sexuality. Some of the impairments or limitations that may be identified during an objective assessment can have an impact on sexual function and it is important to be aware of these issues: strength, grip, dexterity, sensibility, pain, bed mobility, motor control, etc. Interventions are presented in detail in the guide regarding physical activity, positioning, muscle weakness, fatigue, decreased mobility, erectile dysfunction, sensitivity disorders, lubrication, pain, incontinence, and cardio and respiratory implications. Conclusions: To the best of our knowledge, this is the first guide on the role of physical therapists in sexuality. Physical therapists should integrate sexual function into their assessments and interventions. They are an essential part of the rehabilitation team, and they should collaborate with other health professionals to have a multidisciplinary approach, especially in NMD patients. More studies are needed to evaluate the effects of intervention on sexual function in this population. Disclosure: No